2015
DOI: 10.15361/1984-5529.2015v43n2p149-155
|View full text |Cite
|
Sign up to set email alerts
|

Development of cv. BRS Novaera cowpea inoculated with rhizobium recommended for pigeonpea

Abstract: The cultivation of cowpea (Vigna unguiculata) has grown in Brazil, especially in the Cerrado of Mato Grosso, where it is produced in off-season. The association of cowpea plants with rhizobia has provided much of the nitrogen required by this culture. This study aimed at evaluating the development of cowpea inoculated with rhizobia recommended for pigeonpea (Cajanus cajan). The experiment was conducted at the Federal University of Mato Grosso, University Campus Rondonópolis-MT under greenhouse conditions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…For Guimarães et al (2011b), upon evaluating the effect of Azospirillum spp. inoculation on the productive characteristics of Brachiaria brizantha cv.…”
Section: Resultsmentioning
confidence: 99%
“…For Guimarães et al (2011b), upon evaluating the effect of Azospirillum spp. inoculation on the productive characteristics of Brachiaria brizantha cv.…”
Section: Resultsmentioning
confidence: 99%
“…However, the assumption is that the indigenous Bradyrhizobia species are capable of nodulating cowpea due to its promiscuous nature, thereby making inoculation with effective strains unnecessary [16]. Recent studies have however disproved this, as reported in Brazil [17,18], Ghana [1,19]; Mozambique [20]; Nigeria [21] and Tanzania [22]. Inoculating cowpea with effective Bradyrhizobia strain could be beneficial, environmentally safe and reduces N fertilizer application due to improved nodulation and N fixation [19].…”
Section: Introductionmentioning
confidence: 99%
“…BNF is shown to be efficient in cowpea and if well nodulated, can achieve high yield levels (Rumjanek et al, 2005). Guimarães et al (2015) reported that cowpea responded significantly to inoculation, with increase in height of plants, number of pods, grain number, number of nodules, length of pods, dry mass of nodules, grain dry mass and dry mass of aerial part which is equal to or greater than the nitrogen fertilization. However, nodulation and BNF are influenced by edaphoclimatic factors that can bring benefits or damages to the process.…”
Section: Introductionmentioning
confidence: 99%